PENGARUH CITRA ORGANISASI, PENETAPAN HARGA DAN KUALITAS LAYANAN TERHADAP KEPUASAN DAN DAMPAKNYA PADA LOYALITAS MAHASISWA - Joniansyah Ilhamuddin; Amri . (JEM Jurnal Ekonomi dan Manajemen, 2018)
This study aims to examine the effect of the organizational image, pricing and service quality on satisfaction and its impact on the loyalty of students of law study programs at the College of Law in Bangka Pangkalpinang College. The study was conducted on 193 students of STIH Pertiba who were registered as active students. This study uses a path analysis model to examine the relationship between variables hypothesized. The results of the study conclude that organizational image, pricing and service quality contribute to student satisfaction. Organizational image variables provide the greatest contribution to student satisfaction. Satisfied students also have a big impact on their loyalty to the Pertiba STIH. The results of this study can be a reference for researchers who are interested in the same topic, and as material for further research in a deeper and wider scope by adding other independent and dependent variables to be examined